2007
DOI: 10.1021/ac062155g
|View full text |Cite
|
Sign up to set email alerts
|

Halo Ion Trap Mass Spectrometer

Abstract: We describe a novel radio frequency ion trap mass analyzer based on toroidal trapping geometry and microfabrication technology. The device, called the halo ion trap, consists of two parallel ceramic plates, the facing surfaces of which are imprinted with sets of concentric ring electrodes. Radii of the imprinted rings range from 5 to 12 mm, and the spacing between the plates is 4 mm. Unlike conventional ion traps, in which hyperbolic metal electrodes establish equipotential boundary conditions, electric fields… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
99
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(102 citation statements)
references
References 28 publications
0
99
0
1
Order By: Relevance
“…Welling and co-workers used this method, which they termed "secular scanning", to obtain higher resolution mass spectra when compared to q scanning in a linear ion trap (the resonance was quadrupolar over a limited mass range and with slow frequency scanning) [27], Roth and coworkers used secular frequency scanning in a linear trap for mass selective excitation [28], and the Austin group at Brigham Young University used it to scan ions out of the halo ion trap [29][30][31]. Note that in the case of the halo trap, the geometry of the device necessitated the use of AC frequency scanning because simulations indicated that a conventional rf amplitude ramp would cause ions to collide with the electrodes and ceramic holders instead of being ejected out the apertures in the electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Welling and co-workers used this method, which they termed "secular scanning", to obtain higher resolution mass spectra when compared to q scanning in a linear ion trap (the resonance was quadrupolar over a limited mass range and with slow frequency scanning) [27], Roth and coworkers used secular frequency scanning in a linear trap for mass selective excitation [28], and the Austin group at Brigham Young University used it to scan ions out of the halo ion trap [29][30][31]. Note that in the case of the halo trap, the geometry of the device necessitated the use of AC frequency scanning because simulations indicated that a conventional rf amplitude ramp would cause ions to collide with the electrodes and ceramic holders instead of being ejected out the apertures in the electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Major efforts have been made to miniaturize capillary GC [10 -14] and most MS analyzers, including time-of-flight (TOF) [15][16][17], quadrupole [18], magnetic sector [17][18][19], Fourier transform ion cyclotron resonance (FTICR) [20], and cylindrical [21][22][23], rectilinear [24 -26], and toroidal [27,28] ion traps. Most of these reports have concentrated on miniaturizing the GC column or the mass analyzer.…”
mentioning
confidence: 99%
“…One limitation to miniaturizing ion traps is reduction in ion storage capacity. However, this reduction can be ameliorated by trapping ions in a toroidal geometry [27,28,39].…”
mentioning
confidence: 99%
“…The simplified geometry of a cylindrical ion trap in comparison to 3D ion traps has led to a significant research investment in the miniaturization of ion traps [21][22][23][24][25][26] and micro-fabricated ion trap arrays [27][28][29]. Lammert [30,31] and Austin [32][33][34] have studied toroidal ion traps of various geometries in an attempt to expand the quantitative dynamic range of ion traps in miniature and portable instruments.…”
Section: Introductionmentioning
confidence: 99%